Kiko's room Ang kuwarto ni Kiko - Bravo, Becky (Lampara books, 2011)
"Kiko is only six years old and could yet only count from one to twenty, but he has many more toys than that. His mother tells him to sort out his toys and choose which of those he wants to give away. But iko has a hard time deciding which toys he is ready to part with, so he ends up keeping them all to himself despite his mother's request."